Environmental and Molecular Drivers of the α-Gal Syndrome - Cabezas-Cruz, Alejandro; Hodžić, Adnan; Román-Carrasco, Patricia; Mateos-Hernández, Lourdes; Duscher, Georg Gerhard; Sinha, Deepak Kumar; Hemmer, Wolfgang; Swoboda, Ines; Estrada-Peña, Agustín; de la Fuente, José (Frontiers in Immunology, 2019)
The α-Gal syndrome (AGS) is a type of allergy characterized by an IgE antibody (Ab) response against the carbohydrate Galα1-3Galβ1-(3)4GlcNAc-R (α-Gal), which is present in glycoproteins from tick saliva and tissues of non-catarrhine mammals. Recurrent tick bites induce high levels of anti-α-Gal IgE Abs that mediate delayed hypersensitivity to consumed red meat products in humans. Initially, it was thought that the origin of tick-derived α-Gal was either residual blood meal mammalian glycoproteins containing α-Gal or tick gut bacteria producing this glycan. However, recently tick galactosyltransferases were shown to be involved in α-Gal synthesis with a role in tick and tick-borne pathogen life cycles. Two mechanisms might explain the production of anti-α-Gal IgE Abs after tick bites. The first mechanism proposes that the α-Gal antigen on tick salivary proteins is presented to antigen-presenting cells and B-lymphocytes in the context of Th2 cell-mediated immunity induced by tick saliva. The second mechanism is based on the possibility that tick salivary prostaglandin E2 triggers Immunoglobulin class switching to anti-α-Gal IgE-producing B cells from preexisting mature B cells clones producing anti-α-Gal IgM and/or IgG. Importantly, blood group antigens influence the capacity of the immune system to produce anti-α-Gal Abs which in turn impacts individual susceptibility to AGS. Individuals with blood group B and reduced levels of anti-α-Gal Abs have lower risk to develop AGS. Basophil activation and release of histamine have been implicated in IgE-mediated acquired protective immunity to tick infestations and chronic itch. Basophil reactivity was also found to be higher in patients with AGS when compared to asymptomatic α-Gal sensitized individuals. The link between blood groups and anti-α-Gal immunity which in turn affects resistance to vector-borne pathogens and susceptibility to AGS, suggests a trade-off between susceptibility to AGS and protection to some infectious diseases. The understanding of the environmental and molecular drivers of the immune mechanisms involved in AGS is essential to developing tools for the diagnosis, control and prevention of this growing health problem.